Evolution of the mechanical properties of a cobalt-based alloy under thermal shocks. (March 2020) - Wen, Junxia; Che, Hongyan; Cao, Rui; Dong, Hao; Ye, Youxiong; Zhang, Haiyan; Brechtl, Jamieson; Gao, Yanfei; Liaw, Peter K.
Abstract: A cobalt-base alloy manufactured by hot isostatic pressing sintering (HIP) was investigated in the present work. A series of quenching thermal-shock experiments were carried out to study the effects of thermal-cycle shocks on this new cobalt-based alloy. Scanning Electron Microscope (SEM) and Energy Dispersion Spectrum (EDS) were employed to observe the evolution of microstructures under thermal-shock cycles. Results show that some floccus Co3 W3 C precipitated around the WC particles after several thermal-shock cycles. These precipitates and the carbide particles correspond to the locations with the high-stress concentration. The mechanical properties evolution under thermal-shock cycles was analyzed by Nanoindentation tests. The nanohardness presents no noticeable change with thermal-shock cycles. However, the reduced modulus demonstrates a decreasing trend with the thermal-shock cycles. The variation of the mechanical properties has an unestimated relationship with the residual stress and densities of dislocations caused by thermal shocks. Furthermore, the present work pointed out that the precipitates around the carbides are the places where the thermal fatigue crack initiated. How to deal with the precipitates will be the optimized way for this material. Graphical abstract: Unlabelled Image Highlights: Mechanical properties evolution under thermal shocks was evaluated by nanoindentation tests. Discussed the relations of the residual stress and dislocations with the nanoindentation results Residual stress was calculated by the Suresh model. The carbide particles and precipitates are the most probable locations where the cracks initiate.